The Confirmatory Factor Analysis of Career Interest Determinants among Automotive Vocational Students at Universitas Lancang Kuning - Maulana, Fajar; Nursyafti, Yolana; Ustafiano, Bintha (Universitas Negeri Padang, 2025)
This study examines the factors influencing students’ interest in pursuing industrial careers within the Vocational Education and Automotive Technology Program at Universitas Lancang Kuning Pekanbaru. Using a quantitative approach and confirmatory factor analysis (CFA), data were collected from 74 students across three academic levels. The analysis identified two dominant dimensions: external factors (job opportunities, parental support, industry collaboration) and internal factors (personal interest, technological proficiency, practical experience), which together explained 77.135% of the variance. Variables such as industrial prestige and work environment were excluded due to low significance. The findings emphasize that industrial career interest is shaped by both institutional support and individual readiness. These results provide valuable insights for enhancing vocational education strategies through better stakeholder collaboration and targeted curriculum development.